A Grey DEMATEL Integrated Approach to Determine Third Party Logistics Service Provider Selection Criteria - Ejder Ayçin (Alphanumeric Journal, 2018)

(untitled)
Third-party logistics (3PL) services have seen significant growth in recent years as a result of playing a key role in supply chain management. The demand for 3PL service providers has increased as companies offer better service to their customers, lower costs and gain competitive advantage. This paper includes an application that will help determine the most important criteria in the selection and evaluation of 3PL service providers. The aim of the paper is to be able to determine the selection criteria of the 3PL service providers and the relationships between them, from the point of view of companies already using logistics services outsourcing. For this purpose, grey system theory and DEMATEL approach are integrated in order to describe uncertain and complex decisions with definite numerical values and determine the relations and importance levels between the criteria. The findings revealed interrelations between criteria and presented the most important criteria for 3PL provider selection. It is believed that the results of the paper will help the managers to propose a model that can be implemented with the selection criteria of the 3PL service provider.